Deutsche und italienische Besatzung im Unabhängigen Staat Kroatien - Schmid, Sanela (De Gruyter, 2020)
The "Independent State of Croatia," occupied by Germany and Italy, is a laboratory for investigating Nazi and Fascist notions of empire, occupation, and the enforcement of power. For the first time, Sanela Schmid draws on a broad set of sources from German, Italian, and post-Yugoslav archives to examine the two occupation regions that divided Croatia until the Italian capitulation.